30 years on warfarin: a patient's perspective. (2nd October 2020) - Smith, Lowri
Abstract : In this month's patient story, Lowri Smith shares her experience of 30 years on warfarin, including reflections on self-testing and the importance of self-advocating as a patient with a long-term heart condition.